A unified method for calculating the fire resistance of concrete-filled steel tube with fire protection under combined loading. (May 2020) - Yu, Min; Hu, Xuan; Chi, Yin; Ye, Jianqiao
Abstract: Prediction of temperature field is a critical step in the fire resistance design of concrete filled steel tubes (CFST). Theoretically, this step is to solve a transient heat conduction problem defined in a composite medium, of which analytical solutions are either very complex or not available in an explicit form. Though the problem can be solved satisfactorily by various numerical methods, it is not easy and convenient for engineers to implement the methods in practical design or include them in design codes. It has been shown recently, instead of calculating the distribution of temperature, the average temperature over the cross section of a CFST can be used in the calculation of its fire resistance. Based on the average temperature, this paper aims at providing a unified analytical solution for calculating fire resistance of circular and equilateral polygonal CFST columns with or without protection. A simplified method for calculating average temperature over a CFST cross section with or without protective coating is developed and validated, which can take the effect of cross sectional shape and material thermal properties into consideration. The simple temperature calculation method is incorporated into the unified method to calculate the fire resistance of CFST columns with or without protective coating. Comparisons are made between the calculation results using the new equations with those from other existing methods and experiments, which suggest that the newly developed unified method can predict the average temperature and the fire resistance f CFST columns satisfactorily. Highlights: A unified fire resistance calculation method is proposed for protected/unprotected CFST columns based on average temperature An explicit calculation method for average temperature of the steel tube and the concrete core is established. A unified method for both solid and hollow CFST columns with circular/equilateral polygonal cross sections The proposed method is valid for CFST columns with a range of protective coating materials.